Abstracts in social gerontology. (Sage Periodicals Press, 1993)
Classified arrangement of literature consisting of "books, articles, pamphlets, government publications, legislative research studies, as well as other fugitive material." Entries give biographical information, keywords, and abstracts. Also contains a section on related citations. Author and subject indexes.